Peer learning to scale uptake of climate smart practices in Baringo County, Kenya - Bullock, Renee M.; Majiwa, Hamilton; Saalu, Faith; Mundia, Julius; Mbithi, Daniel; Mutai, Samuel (2024)
There is an increased relevance and urgency to support uptake of climate smart agriculture and more so in drylands where water is already scarce. Changes in rainfall patterns and decreased rainfall have been reported in Kenya. Scaling climate smart practices in combination with support from climate information can improve resilience capacities of households and communities in the face of climate change. In the face of increased demand for agricultural information and the reduced capacity of extension systems, many extension providers have been using farmer to-farmer extension (F2FE) that is defined as the provision of training by farmers to farmers (Scarbourough 1997, in Franzel, Kiptot, and Degrande :277). Peer to peer learning approaches are a mutual learning and training strategy that supports collaborative learning. The approach facilitates peers’ learning and, like other peer education approaches, aims to induce behavior changes related to a particular issue of concern (Heidenreich and Breukers 2020). Peer education can have impacts upon peers themselves as well as at the broader societal level by “stimulating collective action that contributes to individual change as well as changes in programs and policies” (Kerrigan and Weiss, 2000). This brief details activities from a peer-to-peer learning event that brought together farmers and agro-pastoralists from dryland counties to learn from each other about climate information services and climate smart agricultural practices that can enhance resilience. Due to low literacy rates and low exposure to new practices, exchange visits are envisioned as an important way to share skills and build capacities with community members from Baringo county locations.